Portuguese vs international millennials: How do their conflict management styles differ? - Falcão, P.; Ferreira, A.; Costa, R. (Proceedings of the International Conference of Applied Business and Management (ICABM2020), 2020)
The purpose of this paper is to analyze how conflict management styles are valued and used differently by Portuguese and International Millennials.